1983
DOI: 10.1063/1.94423
|View full text |Cite
|
Sign up to set email alerts
|

Low-loss integrated optical waveguides fabricated by nitrogen ion implantation

Abstract: A technique for fabricating low-loss (on the order of 0.1 dB/cm) integrated optical waveguides in amorphous SiO2-based material by nitrogen ion implantation is reported. By comparing the results of nitrogen implantation and oxygen implantation in SiO2, the mechanism of waveguide formation in the nitrogen-implanted waveguides is shown to be chemical doping effect of the nitrogen dissolved in amorphous SiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…5,6 Implantation of nitrogen produces a large change in n which has been attributed to the formation of silicon oxynitride. [7][8][9][10][11] While coatings are the common method of changing the reflection or absorption of glass, little work has been done concerning the formation of specific buried compounds and their effects on optical properties. In this article, we report on the formation of a crystalline TiN phase by sequential implantation of Ti and N above a threshold dose.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Implantation of nitrogen produces a large change in n which has been attributed to the formation of silicon oxynitride. [7][8][9][10][11] While coatings are the common method of changing the reflection or absorption of glass, little work has been done concerning the formation of specific buried compounds and their effects on optical properties. In this article, we report on the formation of a crystalline TiN phase by sequential implantation of Ti and N above a threshold dose.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, it is possible to form new compounds (chemical interaction), which originate in regions with very large differences in the refractive-index with respect to the substrate [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The large increase in the index of refraction was attributed to the formation of Si-O-N bonds. Naik demonstrated that N implantation in silica can be used to fabricate low loss integrated waveguides [11].…”
Section: Introductionmentioning
confidence: 99%